Full-length RNA sequencing and single-nucleus sequencing deciphers programmed cell death and developmental trajectories in laticiferous canals of Decaisnea insignis fruits - Li, Gen; Zhao, Qian; Shi, Xinwei; Li, Bin; Yang, Luyao; Wang, Yanwen; Zhou, Yafu (Frontiers in Plant Science, 2024)
Abstract：Programmed cell death (PCD) is a fundamental biological process crucial for plant development. Despite recent advancements in our understanding of PCD's molecular mechanisms, the intricate orchestration of this process within plant cells remains enigmatic. To address this knowledge gap, the present study focuses on Decaisnea insignis, a plant species renowned for its unique fruit anatomy, including laticiferous canals that secrete latex. While extensive anatomical studies have elucidated the structural features of these canals, molecular insights into their developmental regulation, particularly the involvement of PCD, are lacking. Using sequencing technology combining full-length RNA sequencing and single-nucleus RNA sequencing (snRNA-seq) in combination with ultrastructural analyses, our study revealed a cellular map of Decaisnea insignis fruit at the single-cell level and identified different cell types. In particular, we identified a possible PCD-mediated cluster of Decaisnea insignis fruit lactiferous canals in epidermal cells and clarified the expression patterns of DiRD21A (a hydrolase) and DiLSD1 (a transcription factor), which may be closely related to the development of laticiferous canals in Decaisnea insignis fruits. By integrating high-resolution gene expression profiling with visual insights into cellular transformations, we sought to more precisely characterize the regulatory role of PCD during the developmental formation of lactiferous canals in Decaisnea insignis fruit.